2011
DOI: 10.1038/labinvest.2010.136
|View full text |Cite
|
Sign up to set email alerts
|

HGF/c-Met pathway has a prominent role in mediating antiapoptotic signals through AKT in epithelial ovarian carcinoma

Abstract: The Met receptor tyrosine kinase and its ligand, hepatocyte growth factor (HGF), are overexpressed and/or activated in a variety of human malignancies. However, its role in epithelial ovarian carcinoma (EOC) has not been clearly elucidated. Therefore, we investigated the role of HGF/c-Met signaling pathway in a large series (156) of Saudi EOC patient samples, a panel of cell lines, and xenografts in a NUDE mouse model. Using immunohistochemistry, c-Met overexpression was found in 27.2% Middle Eastern EOC sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Previously, p-Met activation secondary to HGF stimulation required low doses of PHA665752 40 ; however, when p-Met is constitutively activated, higher doses of PHA665752 are required. 41,42 We have also previously shown that treatment with PHA665752 at doses of 1 and 5 mol/L does not affect the phosphorylation status of other proteins, such as pLyn, p-Stat3, p-Jak2, and p-SRC, in epithelial ovarian cancer. 41 Therefore, we selected working doses of 1 and 5 mol/L of PHA665752 for our in vitro experiments.…”
Section: P-met Inactivation Inhibited Cell Viability and Induced Apopmentioning
confidence: 81%
See 1 more Smart Citation
“…Previously, p-Met activation secondary to HGF stimulation required low doses of PHA665752 40 ; however, when p-Met is constitutively activated, higher doses of PHA665752 are required. 41,42 We have also previously shown that treatment with PHA665752 at doses of 1 and 5 mol/L does not affect the phosphorylation status of other proteins, such as pLyn, p-Stat3, p-Jak2, and p-SRC, in epithelial ovarian cancer. 41 Therefore, we selected working doses of 1 and 5 mol/L of PHA665752 for our in vitro experiments.…”
Section: P-met Inactivation Inhibited Cell Viability and Induced Apopmentioning
confidence: 81%
“…41,42 We have also previously shown that treatment with PHA665752 at doses of 1 and 5 mol/L does not affect the phosphorylation status of other proteins, such as pLyn, p-Stat3, p-Jak2, and p-SRC, in epithelial ovarian cancer. 41 Therefore, we selected working doses of 1 and 5 mol/L of PHA665752 for our in vitro experiments. Next, we treated CRC cell lines with 1 and 5 mol/L of PHA665752, and cell cycle fractions were analyzed by flow cytometry.…”
Section: P-met Inactivation Inhibited Cell Viability and Induced Apopmentioning
confidence: 81%
“…In recent years, mis-regulation of the HGF/cMET pathway has been investigated in ovarian cancer, and high expression of cMET has been identified in subsets of all four major histotypes of EOC (high grade serous, clear cell, mucinous, and endometrioid [22][23][24][25][26][27][28][29]). It must be noted, however, that the outcome from this over-expression remains unclear.…”
Section: Hgf/cmet In Ovarian Cancermentioning
confidence: 99%
“…For example, recent IHC studies performed on gastric tumour samples have reported cMET over-expression in 4-63% of cases [72][73][74][75][76][77] and various studies performed in ovarian cancer estimate high expression of cMET to be present in 11-68 % of cases [30,22,23,26,25] (Table 1). The majority of the estimates above come from IHC studies, using a number of different antibodies, but no consensus on scoring criteria yet exists, nor whether cytoplasmic or membranous staining for cMET is important.…”
Section: Ihc For Cmetmentioning
confidence: 99%
See 1 more Smart Citation